PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH PADA MATA PELAJARAN PAI-BP DI SDN 1 PANGGUNG - Mohammad Arief (ADISAM PUBLISHER, 2026)
A learning model is a framework for learning activities created by teachers to help students develop their potential. The learning model covers all aspects of the presentation of learning materials, including the supporting facilities used. Choosing the right learning model can support the achievement of learning objectives in the classroom. The PAI-BP subject contains religious foundations and Islamic moral values. Therefore, a learning model is needed that can help teachers and students in developing learning activities and creativity. One of the effective learning models to be applied to the PAI-BP subject is the Make a match learning model. Because this learning model can create student activity in acquiring intellectual skills, attitudes, and motor skills. In addition, it can generate positive responses, can create better interactions between friends, and can instill an attitude of self-confidence and responsibility. PAI-BP learning with the Make a match learning model provides students with the opportunity to practice expressing opinions, speaking, and self- confidence so as to create a pleasant atmosphere.